Optical emission of 223Radium: in vitro and in vivo preclinical applications. Issue 4 (18th December 2017) - Boschi, Federico; De Sanctis, Francesco; Spinelli, Antonello E.
Abstract : 223 Radium ( 223 Ra) is widely used in nuclear medicine to treat patients with osseous metastatic prostate cancer. In clinical practice 223 Ra cannot be imaged directly; however, gamma photons produced by its short‐lived daughter nuclides can be captured by conventional gamma cameras. In this work, we show that 223 Ra and its short‐lived daughter nuclides can be detected with optical imaging techniques. The light emission of 223 Ra was investigated in vitro using different setups in order to clarify the mechanism of light production. The results demonstrate that the luminescence of the 223 Ra chloride solution, usually employed in clinical treatments, is compatible with Cerenkov luminescence having an emission spectrum that is almost indistinguishable from CR one. This study proves that luminescence imaging can be successfully employed to detect 223 Ra in vivo in mice by imaging whole body 223 Ra biodistribution and more precisely its uptake in bones. Abstract : This study shows the decay of 223 Radium ( 223 Ra) as source of optical light. The emission, mostly generated by its short‐lived daughter nuclides, is compatible with Cerenkov radiation (CR). The uptake of 223 Ra, especially in bones, is shown here by whole body optical imaging technique in mice. This discovery will provide a new tool for in vivo tracking of 223 Ra with widely available optical instruments for preclinical research.